HUBUNGAN MOBILISASI DINI DENGAN PENYEMBUHAN LUKA POST SECTIO CAESAREA PADA IBU NIFAS - Siregar, Marni; Panggabean, Hetty (UNIVERSITAS SARI MUTIARA INDONESIA, 2018)
What affects the healing of post-partum wounds includes blood supply, infection and irritation, with early mobilization.The purpose of this study was to determine the relationship between early mobilization and post sectio caesarean wound healing in postpartum mothers at Tarutung Hospital. This study used the Cronbach's Alpha method. The population was all post sc mothers in Tarutung Hospital from June to August 2018 as many as 33 people. The sample technique is accidental sampling. Research variables, independent variables early mobilization and dependent variable post sectio caesarean wound healing in postpartum mothers.Based on the results of the analysis, Ho is rejected, it means that it can be concluded that there is a relationship between early mobilization and post-SC wound healing in postpartum mothers. The results of statistical tests carried out by SPSS with the Wilconxon Match Pairtest formula on 33 respondents calculated using a computer showed that a Z value of showed a relationship between early mobilization and wound healing, where the value was (p - 0.03)